Les proverbes kabyles : les facteurs d’une déperdition - Rabiha Ait Hamou Ali (Multilinguales)
The durability of the Kabyle proverb Experiences a weakening collateral to that of the chain of its intergenerational transmission agents. With the redistribution of social tasks witch the nuclear family Generalizes and the educational demand for social success, Kabyle proverbs seem to persist rather than resist despite the popular mobilization in Kabylia for Amazighity.